Endothelial TFEB (Transcription Factor EB) Restrains IKK (IκB Kinase)-p65 Pathway to Attenuate Vascular Inflammation in Diabetic db/db Mice. Issue 4 (April 2019) - Song, Wencong; Zhang, Cheng-Lin; Gou, Lingshan; He, Lei; Gong, Yao-Yu; Qu, Dan; Zhao, Lei; Jin, Nana; Chan, Ting Fung; Wang, Li; Tian, Xiao Yu; Luo, Jiang-Yun; et al.
Abstract : Objective—: TFEB (transcription factor EB) was recently reported to be induced by atheroprotective laminar flow and play an anti-atherosclerotic role by inhibiting inflammation in endothelial cells (ECs). This study aims to investigate whether TFEB regulates endothelial inflammation in diabetic db/db mice and the molecular mechanisms involved. Approach and Results—: Endothelial denudation shows that TFEB is mainly expressed in ECs in mouse aortas. Western blotting shows TFEB total protein level decreases whereas the p-TFEB S142 (phosphorylated form of TFEB) increases in db/db mouse aortas, suggesting a decreased TFEB activity. Adenoviral TFEB overexpression reduces endothelial inflammation as evidenced by decreased expression of vascular inflammatory markers in db/db mouse aortas, and reduced expression of a wide range of adhesion molecules and chemokines in human umbilical vein ECs. Monocyte attachment assay shows TFEB suppresses monocyte adhesion to human umbilical vein ECs. RNA sequencing of TFEB-overexpressed human umbilical vein ECs suggested TFEB inhibits NF-κB (nuclear factor-kappa B) signaling. Indeed, luciferase assay shows TFEB suppresses NF-κB transcriptional activity. Mechanistically, TFEB suppresses IKK (IκB kinase) activity to protect IκB-α from degradation, leading to reduced p65 nuclear translocation. Inhibition of IKK by PS-1145 abolished TFEB silencing-induced inflammation in human umbilical vein ECs. Lastly, we identified KLF2 (Krüppel-like factor 2) upregulates TFEB expression and promoter activity. Laminar flow experiment showed that KLF2 is required for TFEB induction by laminar flow and TFEB is an anti-inflammatory effector downstream of laminar flow-KLF2 signaling in ECs. Conclusions—: These findings suggest that TFEB exerts anti-inflammatory effects in diabetic mice and such function in ECs is achieved by inhibiting IKK activity and increasing IκBα level to suppress NF-κB activity. KLF2 mediates TFEB upregulation in response to laminar flow. Abstract : Supplemental Digital Content is available in the text.